Analisis Nilai-Nilai Pendidikan Islam dalam Tradisi Molodhen Masyarakat Madura - Diana Annabila; Dimo Aditia Nugroho; Fitri Nursani Rofifah Supriyadi; Ghefira Sakina Koto; Hendri Asri Harahap (Jurnal Budi Pekerti Agama Islam, 2025)
The Molodhen tradition is one of the ways to celebrate the birth of Prophet Muhammad SAW, which is still preserved by the Madurese community to this day. This tradition is not only rich in religious meaning but also contains several crucial Islamic educational values for shaping the character of the community. This study aims to examine the Islamic educational values found in the Molodhen tradition, including values of cooperation, empathy and social care, creativity and aesthetics, as well as educational values. The results of the analysis show that the value of cooperation is evident in the community's togetherness during event preparations, the values of empathy and social care appear through the habit of helping each other and sharing sustenance, the values of creativity and aesthetics can be seen from the beauty of decorations and showcased art, and the educational value is reflected in instilling religious attitudes, a sense of responsibility, and togetherness among the younger generation.  Thus, the Molodhen tradition plays a significant role as a tool for social and spiritual learning that reinforces Islamic values in the life of the Madurese community.